SOSIALISASI DAN PELATIHAN MENINGKATKAN NILAI TAMBAH LABU SIAM MENJADI SELAI - Kamarudin, Anna Permatasari; Yusnadi, Alja; Amna, Amna; Novandi, Idham; Muhtadi, Muhtadi (DEVELOPMENT: Journal of Community Engagement, 2025)
Timang Gajah Village is a village in Bener Meriah Regency. The dominant garden produce is almost all the vegetables and fruits that commonly grow and are suitable for plating in Bener Meriah and central Aceh. One of them is chayote. Until now, chayote has only been used as a vegetable. Furthermore, the price of chayote is quite cheap. However, many products can be produced from chayote, one of which is jam. Jam can be used as a spread on bread and cakes. The purpose of this Community Service is to find solutions for utilizing and increasing the economic value of chayote. This Community Service implementation was attended by 15 mothers from the general public. The methods used in this implementation were counseling and demonstrations. The results of the Pre-Test and Post Test showed an increase in knowledge among partners regarding the use and processing of chayote jam. Especially regarding chayote can be processed into products other than vegetables and chayote can produce chayote jam. The resulting jam can be used personally or used as a home industry. The implementation evaluation showed that almost all partners stated ‘Strongly Agree’ to several statements.